Online learning environment surveys for higher education : comparative analysis and future research - Jesus, Ângelo (2011)
The quality of the environment in which students learn, plays a paramount role. Researchers and education practioners should have means by which they can measure the learning environment before they can enact any changes in that environment that will lead to improving the effetiveness of education. Learning environments questionnaires have been utilized in multiple countries at multiple educational levels and many educational areas, however there are no records of such instruments being validated and used in Portugal. The aim of this integrative review is to analyze several questionnaires/instruments designed for the evaluation of learning environments, in order to make a critical appreciation about the assessed dimensions and finally establish an action plan for the adaptation and cross-cultural validation of one of these instruments for the Portuguese Language.